Effect of Chlorpyrifos on the Red Blood Cells Morphology of Common Carp (Cyprinus Carpio): A Hematological Study - Akram, Wasim; Rab Nawaz; Kifayat Ullah; Sayyed, Hammad Ullah; Muhammad Khisroon (Indus Journal of Bioscience Research, 2024)
Chlorpyrifos, a widely applied insecticide, enters waterways through runoff, affecting a wide range of aquatic species. The environmental impact of chlorpyrifos (CPF), a commonly used organophosphate pesticide, on aquatic organisms remains a significant concern due to its toxicity and persistence in ecosystems. This study evaluates the effects of CPF on the morphology of red blood cells (RBCs) in the common carp (Cyprinus carpio) to better understand its hematological toxicity. Common Carp were exposed to sublethal concentrations of CPF (0, 10, 20, and 30 µL) for duration of seven days. Blood samples were collected and examined for alterations in RBC morphology. Control specimens showed minimal morphological changes which were due to natural conditions, while CPF exposure induced a concentration-dependent increase in cellular abnormalities, including double nucleated cells, nuclear displacement, cell deformation, and fragmentation. The highest CPF concentration (30 µL) resulted in severe RBC damage, including nuclear pyknosis, loss of cell integrity, and necrosis. These findings suggest that CPF exposure leads to significant erythrocyte damage, which may compromise overall fish health and survival. The results underscore the need for stringent environmental monitoring and regulation of pesticide use to mitigate its detrimental effects on aquatic life.